YARN DEVELOPMENT FROM RICE STRAW TO COMMERCIAL - Hattayananont, Autcha; Theeramongkol, Praparnporn; Sioyraya, Bussara (MATTER: International Journal of Science and Technology, 2017)
This research studied the process of separating fibers from rice straw. To study the physical properties of fibers from rice straw and the process of manufacturing yarn from rice straw fibers. It was analyzed by physical textile testing laboratory and developed as woven and into commercial products. The process of separating fibers from dried rice straw and selected the rice straw fiber length at least 30 cm. To subtract and peel off the joints of the lower end by hand. The result in the physical laboratory, it is cellulose fibers, tensile strength (Newton) at 28.18, elongation (percent) is at 2.01 which is cross-section; oval and clearly and its length is smooth and transparent. There are metals plenty of CADMIUM and LEAD at 0.1 mg/kg, CHROMIUM (TOTAL) / (VI) and COPPER at 0.5 mg/kg. There are 2 warps yarn and using natural color without blench. When woven as a fabric to develop for 4 products prototype: table lamps, tablecloths in Japanese style, potted plants and Accessories Box.